Conditions of sex ratio and growth patterns of craft (Portunus pelagicus) in the waters of Kawal village, Bintan Regency, Riau Island Province - Hardi Wiradinata; Wahyu Muzammil; Susiana Susiana; Rochmady Rochmady (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2022)
Business Crab (Portunus pelagicus) Kawal Village waters are waters located in the Gunung Kijang area, Bintan Regency, Riau Islands Province. High market demand for crab fishery commodities that triggers excessive exploitation so that it can have an impact on the sustainability of crab resources. This study aims to determine the condition of the sex ratio and the pattern of crab growth in the waters of Kawal Village, Bintan Regency. The method used in this study is a survey method. The sampling technique was carried out using a random census, in which the researcher immediately went down to the field to take a sample of 176 crabs. The results showed a good sex ratio for female crabs at 52% and male crabs at 48%, which has calculated the Chi-square test which between females and males has a balanced ratio, which results in: X2 count of 33, 2 while X table is 74,975 which if X2 count < X table: male and female sex ratio is balanced. The growth pattern of both female and male crabs in the waters of Kawal Village, Bintan Regency has a negative allometric character where the growth pattern of carapace width is greater than weight growth.